The role of nearshore slope on cross-shore surface transport during a coastal upwelling event in Gulf of Finland, Baltic Sea. (30th September 2018) - Delpeche-Ellmann, Nicole; Soomere, Tarmo; Kudryavtseva, Nadezhda
Abstract: The wind induced coastal upwelling process often contains a mid-phase that involves coherent long-living cross-shore surface jets of cooler water. These jets extend to 40–45 km from the coast and tend to start from particular coastal locations. We develop a simple method for evaluating the depth in the water column from where the upwelled water originates. We also test the hypothesis that the development of cross-shore surface jets may be triggered by some permanent characteristics such as the bathymetry or the slope of the nearshore seabed. The analysis is performed for a strong and well-documented upwelling in the Gulf of Finland, the Baltic Sea, using high resolution bathymetry data, satellite derived sea surface temperature, surface currents measured by in situ drifters, and properties of water masses in two sampling locations. The results indicate that the cross-shore jets originate exclusively from the shore sections with much steeper slopes (>0.0075) than in the rest of the study area. The cooler water most likely origins from intermediate water masses at depths between 15 and 30 m. The resulting identification of the source depth of the upwelled water and its spatial location assists in understanding the flux of nutrients during upwelling events and their link to the onset of cyanobacteria blooms. Highlights: Bathymetry of the offshore plays a major role in the onset of cross-shore jets. Cross-shore upwelling jets likely start from steep nearshore segments. The source depth of upwelled waters may be estimated from the extent of cross-shore jet. This depth discloses the flux of nutrients (phosphates or nitrates) brought up to surface.